Protective Effect of Bioactivity Guided Fractions of Ziziphus jujuba Mill. Root Bark against Hepatic Injury and Chronic Inflammation via Inhibiting Inflammatory Markers and Oxidative Stress - Kandimalla, Raghuram; Dash, Suvakanta; Kalita, Sanjeeb; Choudhury, Bhaswati; Malampati, Sandeep; Kalita, Kasturi; Kalita, Bhupalee; Devi, Rajlakshmi; Kotoky, Jibon (Frontiers in Pharmacology, 2016)
The tribal communities of North Eastern India rely on herbal medicine to cure various disease conditions. Ziziphus jujuba Mill. (Rhamnaceae) is one of such medicinal plants used for curing liver ailments, insomnia, anemia, diarrhea, diabetic complications, cancer and loss of appetite. The present study was aimed to describe the protective ability of Z. jujuba root bark against hepatic injury and chronic inflammation. Bioactivity guided fractionation of Z. jujuba methanol extract (ZJME) was performed using different solvents of increasing polarity viz. hexane (ZJHF), chloroform (ZJCF), ethyl acetate (ZJEAF), water (ZJWF) and residue (ZJMR). In vitro antioxidant results revealed that both ZJME and ZJWF possess strong antioxidant activity among all the fractions and mother extract tested. Further, ZJME and ZJWF showed significant protection against CCl4 intoxicated HepG2 cell lines by means of increased cell viability and decreased LDH levels compared to control group. ZJME at 200, 400 mg/kg and ZJWF at 50, 100 mg/kg inhibited the lipid peroxidation and significantly restored the liver function markers (AST, ALT, ALP, LDH, SOD and CAT) and cytokine levels (TNF-α, Il-1β and Il-10) in CCl4 induced acute liver damage in rats. All the results were comparable with standard drug silymarin which was further confirmed by histopathology analysis of liver. Similarly, inflammation and increase inflammatory cytokines levels of carrageenan induced paw edema in rats have been refurbished to normal levels on par with the standard drug indomethacin. ZJWF demonstrated potent response than ZJME in all the biological tests conducted. The results of the study signify the ability of Z. jujuba root bark as good therapeutic agent for liver toxicity and chronic inflammation.